DEVELOPING A STANDARD ENGLISH LANGUAGE FINAL ACHIEVEMENT TEST INSTRUMENT FOR 8TH GRADE STUDENTS BASED ON THE IMPLEMENTATION OF CURRICULUM 2013 IN KARANGASEM AND BULELENG REGENCY IN 2014/2015 SCHOOL YEAR - ., Ni Wayan Aristiya Dewi; ., Drs.Gede Batan,MA; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian R&D ini bertujuan untuk menyajikan spesifikasi dan pengembangan instrumen tes ulangan kenaikan kelas Bahasa Inggris untuk menilai kompetensi pengetahuan siswa kelas 8 berdasarkan penerapan Kurikulum 2013. Spesifikasi tes dirancang berdasarkan 15 kompetensi dasar bidang pengetahuan dalam silabus kurikulum 2013. Pengembangan tes mengikuti enam prosedur pengembangan tes bahasa standar oleh Brown dan Abeywickrama (2010). Akan tetapi, karena keterbatasan penelitian maka pengembangan tes hanya mengikuti 4 prosedur yaitu 1) menentukan objektif dan tujuan tes, 2) merancang kisi-kisi, 3) merancang tes, dan 4) membuat evaluasi yang sesuai terhadap butir soal (validasi, try-out, dan analisis butir). Proses validasi tes melibatkan dua orang ahli yang hasilnya menyatakan tes tersebut memiliki validitas konstruk dan tampilan yang sangat baik. Uji coba dilakukan dua kali dan analisis buti dilakukan terhadap skor tes siswa untuk mendapatkan hasil tingkat kesusahan, daya pembeda, keefektifan pengecoh, dan homogenitas butir soal. Uji reliabilitas dihitung dengan metode Split half dan hasilnya adalah 0,93. Dari 100 butir soal yang awalnya dirancang, 65 butir soal dinyatakan layak untuk test.Kata Kunci : tes ulangan kenaikan kelas, pengembangan tes, analis butir soal, kurikulum 2013 This R&D study was aimed to present the specification and the development of a standard English Language final achievement test instrument to assess the 8th grade students knowledge competency based on the implementation of Curriculum 2013. The specification of the test was designed based on the 15 basic competencies of knowledge competence in the curriculum 2013 syllabus. The test development followed six procedures of developing standard language test by Brown and Abeywickrama (2010). However, because of the limitation of the study the test development only followed 4 procedures namely 1) determining the objective and purpose of the test, 2) designing the test specification, 3) designing the test, and 4) make appropriate evaluation of different kinds of items (validation, try-outs, and item analysis). The test validation process involved two experts and the result showed that the test has a very good construct and face validity. Try out tests were conducted twice and item analysis was conducted on the students’ test score to get the result of the item facility, item discrimination, distractor efficiency, and item homogeneity. The reliability of the test was calculated with Split half method and found to be 0.93. From 100 questions item that initially designed, 65 question items were accepted for the test. keyword : achievement test, test development, item analysis, curriculum 2013